Regime change in contemporary Turkey politics, rights, mimesis - Polat, Necati 1963- (Edinburgh University Press, 2016)
"Turkey has faced a series of upheavals in its political regime from the mid-nineteenth century. This book details the most recent change, placing it in its broader historical setting. Beginning with the Justice and Development Party's rule from late 2002, supported by a broad informal coalition that included liberals, the book shows how the former Islamists gradually acquired full power between 2007 and 2011. It then describes the subsequent phase, looking at politics and rights under the amorphous new order."--Page [4] of cover.